Developing composites of zinc and hydroxyapatite for degradable orthopedic implant applications. Issue 1 (April 2021) - Mahesh, P.V.S.; Akhil, S.; Chiranjeevi, P.; Sivaji, Y.; Kondaiah, V.V.; Rao, M. Ananda; Dumpala, Ravikumar; Sunil, B. Ratna
Abstract: In the present work, Zn-HA composites were developed by powder metallurgy route targeted for bone implant applicaitons. Zn-HA powders with varying HA content (1, 2, and 4 wt.%) were ball milled for 1 hr and sintered to produce composite compacts. X-ray diffraction (XRD) studies were done for all the ball milled powders and sintered compacts. No impurities were observed in the ball milled powders. Microstructural observations revealed the formation of lamellar structure in the composites due to the plastic deformation of the Zn powders during ball milling. Grain size measurements revealed the decreased grain size with increase of addition of HA. Furthermore, aspect ratio (length to thickness ratio) of the grains was measured and found that the aspect ratio was also decreased with the increased HA content. Higher microhardness was measured for all the composites compared with pure Zn. However, composite with 1% has shown higher hardness compared with the remaining composites. Form the preliminary observations, it can be concluded that Zn-HA composites can be successfully produced with lamellar morphology by ball milling followed by sintering for biomedical applications with increased hardness.